Perception of mothers' towards home visiting after delivery done by health staff and factors influencing it, in Temerloh district, Pahang Darul Makmur. Jun 1999. - Suzana Mohd Hashim; Hanafiah Mohd Salleh (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
This is a study regarding perception of mothers' towards home visiting after delivery done by health staff and factors influencing it. A cross sectional study was done in Temerloh District for 3 weeks involving 202 mothers. These mothers had uncomplicated pregnancy, uncomplicated delivery and had received the last postnatal home visiting from health staff Their names were gathered from birth record book from all the five Health Clinics in the district. Only those who fulfilled the required criteria were chosen as participants. The interview was done in mothers home by 5 trained research assistances. Results showed that 73.3% of mothers had good perception towards reasons why home visiting was done after delivery, 49.0% had good perception towards benefits and 97% had good perception on t quality of the service. The overall good perception of home visiting after delivery done by health staff was 83.2%. Majority of mothers would prefer to received the service from nursing staff, in the morning between 8 am to 11 am, within the first 3 days after delivery and between 5-8 visits. Ninety eight percents perceived that home visiting needs to be done and 82.7% perceived that they and their babies will faced health problems if the service was not carried out. Fifty-five percents admitted having health problems among themselves and their babies within 2 weeks after delivery. Constipation, pain and inflammation at the perineum, mastitis and less milk flow were problems faced by mothers in this study. Problems with defecation, feeding, rashes and jaundice were problems faced by their babies. Eighty percents of health problems were successfully managed by the health staff. Among 82.2% of participants who received help from others in care after delivery, 52.4% was given help by their mothers or motherin- law. Among 82.2% of mothers who practiced traditional belief (pantang larang), 62% claimed that health care given was not contradicting with their 1Iaditional practices. Factors like demography , economy, health problems after delivery, traditional practices, help receive from others and information regarding home visit were factors thought to influence mothers perception on home visiting after delivery .After logistic regression, family income was the only factor that significantly influencing mothers perception towards home visiting after delivery, p = 0.018 ( p < 0.05). In conclusion, home visiting after delivery need to be continued but it also needs review and some modification so that the service can be expanded to other family members as well. Various multidiscipline in medical field have to plan an effective home visiting program to improve the existing service.